Cultural effects in usability assessment - Wee, Alvin Yeo (ACM New York, NY, USA, 1998)
A study is being conducted to identify factors that may affect results of usability evaluation techniques. Preliminary results based on eight subjects are described and then implications of the findings are discussed.